Experimental infection by Salmonella enterica subsp enterica serovar kottbus in day-old broiler chickens - Ribeiro, SAM [UNESP] (2005)
The strain used in this work was a Salmonella enterica subsp enterica serovar Kottbus (6,8:e,h:1,5) isolated from imported day-old ducklings in Laboratório Nacional Agropecuário (LANAGRO/SP) of the Ministry of Agriculture of Brazil (MAPA). In view of the lack of information available about this Salmonella isolate and also because it was detected in day-old imported birds, this study was carried out to investigate the dissemination of S. Kottbus among newly hatched chicks. The birds were placed in three groups: one group of 20 birds received 0.1 mL of S. Kottbus culture containing 1.2 x 10(8) CFU/mL, the second group of 20 birds was inoculated with 1.2 x 10(5) CFU/mL and the third group of 10 birds was untreated (control group). Results were similar for both infected groups. The bacterium was recovered from cloacal swabs collected from the first day following the experimental infection until the end of the trial (42 days post-inoculation). At 15 and 42 days post-inoculation (dpi), half of the birds of each group were killed for bacteriological examination of cecal contents, liver and spleen. At 15 dpi, viable cell counts of S. Kottbus were obtained in all kinds of samples. At 42 dpi, Salmonella was present in the liver and spleen of few birds, but in large amounts in the cecal contents of almost all birds.